2017
DOI: 10.1007/978-3-319-55858-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Annexins: Ca2+ Effectors Determining Membrane Trafficking in the Late Endocytic Compartment

Abstract: Despite the discovery of annexins 40 years ago, we are just beginning to understand some of the functions of these still enigmatic proteins. Defined and characterized by their ability to bind anionic membrane lipids in a Ca-dependent manner, each annexin has to be considered a multifunctional protein, with a multitude of cellular locations and diverse activities. Underlying causes for this considerable functional diversity include their capability to associate with multiple cytosolic and membrane proteins. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 233 publications
0
16
0
Order By: Relevance
“…Depletion of AnxA6 could stabilize StARD3/VAP-A and Rab7/protrudin/VAP-A complexes, ensuring re-establishment of MCS between the ER and late endosomes, and eventually the transfer of late endosome-cholesterol to the ER in cells with non-functional NPC1. Although several annexins contribute to endosomal membrane dynamics [62,96,97], only the AnxA1/S100A11 protein complex has yet been associated with MCS formation [90]. While AnxA2 and AnxA6 are also well known to bind S100 proteins, to our knowledge there is no data linking AnxA2 with MCS [90,98].…”
Section: Discussionmentioning
confidence: 92%
“…Depletion of AnxA6 could stabilize StARD3/VAP-A and Rab7/protrudin/VAP-A complexes, ensuring re-establishment of MCS between the ER and late endosomes, and eventually the transfer of late endosome-cholesterol to the ER in cells with non-functional NPC1. Although several annexins contribute to endosomal membrane dynamics [62,96,97], only the AnxA1/S100A11 protein complex has yet been associated with MCS formation [90]. While AnxA2 and AnxA6 are also well known to bind S100 proteins, to our knowledge there is no data linking AnxA2 with MCS [90,98].…”
Section: Discussionmentioning
confidence: 92%
“…As excess amounts of cellular unesterified (free) cholesterol are cytotoxic, cells have developed sophisticated circuits to regulate its intracellular sorting, trafficking ensure proper LE/Lys functioning and provide opportunity to control the intracellular movement of lipids, in particular, cholesterol, into and out of the LE/Lys compartment. Indeed, we and others demonstrated that AnxA1, A2, A6, and A8 contribute to cholesterol trafficking along endo-and exocytic pathways, suggesting that this subset of annexins, as well as other Ca 2+ -binding proteins, are good candidates for achieving regulatory tasks not only in regard to cellular cholesterol homeostasis, but also cholesterol-dependent activities in LE/Lys such as autophagy [23].…”
Section: Introductionmentioning
confidence: 79%
“…ANXA5 and ANXA6 mediate fusion of autophagosomes/LY and LE/LY, respectively [73]. Other Annexins have been implicated in vesicular membrane trafficking, highlighting them as potential candidates to bridge TPC function and associated SNARE complex activity [72][73][74]. ANKRD27, a regulator of SNARE-and Rab-dependent melanosome enzyme trafficking is also a TPC2 interaction candidate [67].…”
Section: Tpc2mentioning
confidence: 99%